Treatment of chromium bearing wastewater using thermal parametric pumping - Mishra P.K.; Nanagre D.M.; Yadav V.L. (My University, 2025)
Parametric pumping (PP) is an adsorptive separation technique based on periodic, synchronous coupled transport action. Net consequence of the coupling of alternating absorbent fluid position displacements with cycling of a thermodynamic intensive parametric variable (temperature) is a buildup of separation from cycle to cycle. Direct mode of thermal PP was used to separate Cr (VI) from wastewater using low cost adsorbent sawdust carbon. Removal of Cr (VI) decreases as initial concentration increases. For same number of cycles, separation factor increases as upper half cycle temperature increases for same initial concentration of feed. There is an increase in adsorption with increasing pH. A marked increase in separation can be achieved using thermal PP in place of adsorption.